Remembering Gregory Areshian: his years in the United States - Martirosyan-Olshansky, Kristine (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Writing a memorial about a mentor and a dear friend brings a lot of mixed feelings. So many times, I sat down to write and my mind was instantly filled with didactic moments and fond memories, both interweaving, coming to focus, and fading. I tried to maintain a coherent timeline, but my memory pales in comparison to Gregory’s. Few people have been blessed with such impeccable memory.